Meetings: Women teach Women - Kamberidou (Kamp), Irene (Athena Magazine, Publication of the International Studies Association, no 8, Sept. 1986: 258., 1986)
Kamberidou (Kamp), Irene (1986). Meetings: Women teach Women. Athena Magazine, Publication of the International Studies Association, no 8, Sept. 1986: 258. ATHENA MAGAZINE, MONTHLY REVIEW OF CURRENT AFFAIRS.     Publication of the International Studies Association, Athens (1986-1987)                                              Editorial Board:  Dimitris Constas, Vice Rector of the Pantios School of Political Science, Athens; Theodore Couloumbis, Professor of International Relations, University of Thesssaloniki; Paschalis Kitromilides, Associate Professor of Political Science, University of Athens; Christos Rozakis, Professor of International Relations, Pantios School of Political Science; Thanos Veremis, Associate Professor of History, University of Athens   Kamberidou (Kamp), Irene (1987). Beautiful and Shining (Antique Jewellery). Athena Magazine, Publication of the International Studies Association, no. 12, January 1987:24-25.   Kamberidou (Kamp), Irene (1986). Antique fashion is never too old. Athena Magazine, Publication of the International Studies Association, no. 4, May 1986: 132-133.   Kamberidou (Kamp), Irene (1986). Life in Ancient Times. What they wore and how. Athena Magazine, Publication of the International Studies Association, no. 7, August 1986: 240-241. Kamberidou (Kamp), Irene (1986). Meetings: Women teach Women. Athena Magazine, Publication of the International Studies Association, no 8, Sept. 1986: 258.